ANALISIS RESUME MEDIS RAWAT INAP TIDAK LENGKAP DENGAN MENGGUNAKAN KONSEP MASAAKI: SORT, STRAIGHTEN, SCRUB, SYSTEMATIZE, SUSTAIN (5S) DI RSU PARAMA SIDHI SINGARAJA BALI - Pratiwi, IDN Yunita; Wibowo, Adik (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2022)
The quality of the hospital’s medical resume is one of hospital’s services quality indicator, which Parama Sidhi General Hospital still have figure of 17,1% for the incompleteness of medical record data (KLPCM). The goal of this research is to improve the attending physician medical resume’s completion through Sort, Straighten, Scrub, Systematize, and Sustain concept (5S) by acknowledged connection between 5S concept and medical resume completeness efforts based on continues improvement. This research is a mixed method analysis, by using primary and secondary data. The secondary data showed 26,80% among 1362 medical resume files were not completed. Univariate analysis of the medical resumes displayed 1,8% incompletion administrative data, whereas 19,2% final diagnosis and 26% working diagnosis uncomplete as the minor and one of major issues from the clinical data perspective. Univariate analysis of primary data used 5S implementation questionnaire instrument showed that Scrub (S3) 81% and Systematize (S4) 19% as the most common and the least implemented component of 5S, called improvements at re-evaluation of the Standard Operating Procedures (SOP) implementation and its socialization, forms formatting and its filing mechanism, and hospital’s service policy to overcome the physician’s time shortage.